Human Centered Design-Based Logo Design Strategy to Improve the Visual Identity of MSMEs in Pematang Serai Village - Mohammad Yusup; Arpan; Aidil Ahmad (Yayasan Sinergi Multidimensi Kreatif, 2024)
This article examines the crucial role of Human-Centered Design (HCD) in logo development, particularly for Micro, Small, and Medium Enterprises (MSMEs) in Pematang Serai Village. The study highlights the importance of building a strong brand image and explores how HCD principles influence the entire design process—from conceptualization to implementation. The iterative and user-centered nature of HCD ensures continuous refinement of the logo based on real user feedback. This article also discusses visual elements in logo design and their impact on audience perception, recognizing the logo as a significant visual cue in shaping consumer behavior. Furthermore, cultural considerations are emphasized through cross-cultural analysis, underlining the need to adapt logo designs to local contexts—especially relevant for MSMEs in Pematang Serai Village. The findings lead to actionable recommendations for MSMEs, including a user-centered design approach, emphasis on visual appeal, cultural sensitivity, iterative refinement, and strategic logo implementation. This study underscores that applying HCD principles can result in logo designs that are not only visually appealing but also emotionally resonant with the target audience, thereby contributing to sustainable business success.